An experimental performance evaluation and compatibility study of the bluetooth low energy based platform for ECG monitoring in WBANs - Touati, Farid (Hindawi Publishing Corporation, 2015)
A long term healthcare monitoring system requires battery operated devices with low-power technologies. Researchers tried to adapt various short-range technologies for Wireless Body Area Networks (WBANs) in ubiquitous health monitoring. The classical Bluetooth is known for its greedy power consumption, IrDA and NFC require line-of-sight conditions, and ANT has weak coexistence features and interference issues. A typical choice remains ZigBee/6LoWPAN over IEEE 802.15.4 based solutions in WBANs because of their low-power consumption. However, the recently proposed Bluetooth Low Energy (BLE) announced more compelling features in various aspects. Only few studies have been published supporting these claims on BLE. In this paper, we present a BLE based remote healthcare monitoring platform and we study its compatibility for ECG monitoring. ECG data requires continuous and real-time transmissions, making it particularly challenging for resource constrained devices. In our system, a BLE112 module from Blue giga and a BLE USB dongle are used for WBAN. The performance of the system is evaluated experimentally and the results showed good potential of this proposed BLE platform in meeting the main QoS requirements of medical applications in terms of throughput, end-to-end delay, and packet error rate, while staying energy efficient.